CHANGING CAREER DIRECTION FROM HIGHER EDUCATION TO VOCATIONAL EDUCATION AND TRAINING - Kaminskiene, Lina; Bertašiūtė, Judita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The article discusses the problem of overeducation which is described as a situation when individuals gain education higher than required in the labour market and, thus, fall into the so-called opportunity trap (Brown et al., 2011). Individuals’ investment into their education does not meet the expectations: they must expand their career opportunities by changing a career direction towards vocational training. The article aims to reveal the reasons that lead to such a situation. The case analysis revealed three periods which characterize and explain transformations in individuals’ considerations about the value of education and qualification. The 1st period describes a transition of graduates from secondary school to higher education institution. It reveals factors determining the choice of higher education institution. The 2nd period describes experiences of students in higher education system until changing their career for vocational training.  The 3rd period reveals main reasons and factors of students’ choices.